ON THE PLACE OF Z.M. BABUR SHAH’S WORK IN WORLD SCIENCE - Tilavova Guljahon (Zeta Repository, 2023)
The work of Zahiriddin Muhammad Babur - "Baburnoma" is a unique treasure that made a great contribution to the culture of the East is considered. "Boburnoma" is an encyclopedic work that includes knowledge about history, literature, ethnology, political science, art science and natural science. Valuable information about historical careers and individuals is also found in this work. The article also gives some comments about the value of the work, the events in it, and Babur’s creative activity.